Community structure, threats and conservation issues of migratory birds in the south-central coastal area of Bangladesh - Jaman, Mohammad Firoj; Shome, Ashikur Rahman; Rabbe, Md Fazle; Ahmed, Abir; Mia, Tanvir; Hossain , Md Sakhawat; Alam, Md Mahabub (Dhaka University Journal of Biological Sciences, 2025)
The coastal areas of Bangladesh are enriched with migratory avian species but the actual status of birds was unknown, particularly in the south-central coastal region of the country. A yearlong (June 2023 to May 2024) direct field observation-based study was conducted to unfold the present status of the migratory avifauna in three protected areas (Kuakata National Park, Tangragiri Wildlife Sanctuary, and Sonarchar Wildlife Sanctuary). In this study, a total of 85 migratory bird species were recorded under 10 orders and 22 families. Individuals of wetland dependent migratory birds were higher than other bird species. Sonarchar Wildlife Sanctuary (SWS) had the highest number of bird species and individuals (70 species; n = 3618 individuals) with the highest diversity index values (H’ = 3.135, Ds = 0.9257) compared to two other sites. Significant variations among migratory avian communities were found among the three study sites as indicated by the Analysis of Similarity (ANOSIM) test (R = 0.168, P < 0.001) in the non-metric multidimensional plot (NMDs). Among the migratory bird species, Charadrius dubius (14.75%), Anas crecca (14.33%), Threskiornis melanocephalus (11.69%), Actitis hypoleucos 8.47%), Vanellus cinereus (6.75%) were the most abundant. Population abundance was higher for the occurrence of the wetland dependent migratory bird species in the study area. Avian community composition of migratory species showed uneven distribution in the rank abundance curve. Across the three study sites, the majority of the migratory bird species exhibited clumped distribution patterns, followed by regular and random distribution patterns. A total of 37 (45.12%) species of migratory birds were found to use the coastline as their microhabitat. Unplanned fishing, tourism, expansion of agricultural land, hunting, and pollution were identified as major threats to the migratory bird species in the study area. This study suggests community-based conservation measures are essential for the proper conservation of the migratory birds. Dhaka Univ. J. Biol. Sci. 34(1): 155-173, 2025 (January)